Tax Revenue and Income Inequality: A Provincial Level Evidence - Damayanti Sari; Riatu Mariatul Qibthiyyah (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
This study examines the relationship between tax revenues and income inequality at the provincial level in Indonesia from 2011 to 2019. Applying a fixed-effect approach, this study finds that total tax revenue has no significant effect on income inequality. This result implies that Indonesia's current tax system and structure, both national and sub-national, have been unable to contribute to reducing provincial income inequality. Likewise, by the type of taxes, both income tax and value-added tax revenue have a relatively insignificant effect. However, the ratio of local taxes to gross regional domestic product (GRDP) has a considerable positive effect on income inequality, indicating that the majority of consumption taxes in the local tax component are regressive. Accordingly, at the sub-national level, expenditure programs may play role in reducing provincial inequality instead of the tax system.